Effect of Sex Steroids on the Bone Health of Transgender Individuals: A Systematic Review and Meta-Analysis - Singh Ospina, Naykky; Maraka, Spyridoula; Rodríguez Gutiérrez, René; Davidge Pitts, Caroline J.; Nippoldt, Todd B.; Prokop, Larry J.; Murad, Mohammad Hassan (2017)
A comprehensive search of several databases to 7 April 2015 was conducted for studies evaluating bone health in transgender individuals receiving sex steroids. Pairs of reviewers selected and appraised studies. A random effects model was used to pool weighted mean differences and 95% confidence intervals (CIs